Effects and safety of separate low-dose hydrocortisone use in patients with septic shock: A meta-analysis. Issue 1 (January 2020) - Wu, Jing; Huang, Man; Wang, QianWen; Ma, Yuefeng; Jiang, Libing
Objective: The aim of this study was to explore the effects and safety of low-dose hydrocortisone in patients with septic shock. Methods: The PubMed, EMBASE, and Cochrane Central Register of Controlled Trials were searched from database inception until 1 August 2018. Two reviewers performed literature selection, data extraction, and quality evaluation independently. Results: Twelve randomized controlled trials were included in this meta-analysis. The combined results showed that low-dose hydrocortisone use had no survival benefit in patients with septic shock (relative risk = 1.09; 95% confidence interval = 0.88–1.05; P = 0.37). But low-dose hydrocortisone use was useful for shock reverse (relative risk = 1.09; 95% confidence interval = 1.00–1.19; P = 0.04) and in shortening the time of vasopressor support (weighted mean difference = −1.79, 95% confidence interval = −2.05 to −1.52; P < 0.00001). In addition, use of low-dose hydrocortisone was associated with a higher risk of hyperglycemia (relative risk = 1.21; 95% confidence interval = 1.04–1.40; P = 0.01) and hypernatremia (relative risk = 6.34; 95% confidence interval = 1.19–33.81; P = 0.03). There was no significant improvement of intensive care unit mortality (relative risk = 1.11; 95% confidence interval = 0.93–1.33; P = 0.23) or hospital mortality (relative risk = 1.08; 95% confidence interval = 0.94–1.24; P = 0.29), length of intensive care unit (weighted mean difference = −1.84; 95% confidence interval = −5.80 to 2.11; P = 0.36) or length of hospital (weighted mean difference = 0.11; 95% confidence interval = −2.06 to 2.29; P = 0.98), and time of mechanical support (weighted mean difference = −0.69; 95% confidence interval = −1.76 to −0.38; P = 0.20) with the use of low-dose hydrocortisone. There was no significant difference in secondary infection (relative risk = 1.04; 95% confidence interval = 0.91–1.18; P = 0.57), recurrence of shock (relative risk = 1.47; 95% confidence interval = 0.64–3.39; P = 0.36), and gastrointestinal bleeding (relative risk = 1.41; 95% confidence interval = 0.89–2.22; P = 0.14) with the use of low-dose hydrocortisone. Conclusion: Although there was no effect of low-dose hydrocortisone on survival of patients with septic shock, it is associated with a higher rate of shock reversal and shortening duration of vasopressor support; thus, low-dose hydrocortisone may be an alternative drug in septic shock patients who are refractory to fluid resuscitation and vasopressors.